THE WINTER POPULATION OF BIRDS OF ROADSIDE SPACES OF CENTRAL CISCAUCASIA - I. V. MAKIYAN (Юг России: экология, развитие, 2015)
The article provides an analysis of winter roadside avifauna of the Central Сiscaucasia. Observations of birds on the highways are currently one of the most effective, advanced and accessible methods of accounting.